The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/1878-0261.13472
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of circulating tumour DNA in advanced pancreatic ductal adenocarcinoma predicts clinical outcome and reveals disease progression earlier than radiological imaging

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease with a need for better tools to guide treatment selection and follow‐up. The aim of this prospective study was to investigate the prognostic value and treatment monitoring potential of longitudinal circulating tumour DNA (ctDNA) measurements in patients with advanced PDAC undergoing palliative chemotherapy. Using KRAS peptide nucleic acid clamp‐PCR, we measured ctDNA levels in plasma samples obtained at baseline and every 4 weeks during chemotherapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…We found that, using longitudinal analyses of combined mutations of KRAS , TP53 , CDKN2A , SMAD4 , and ARID1A , 48% of the patients had a ctDNA progression earlier than radiologic progression, and 42% a ctDNA progression earlier than CA19-9 progression, both with a median lead time of about 2 months, which is supported by previous reports [ 46 , 79 ]. In resected PDAC, ctDNA could predict recurrence with a median lead time of 84 days.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that, using longitudinal analyses of combined mutations of KRAS , TP53 , CDKN2A , SMAD4 , and ARID1A , 48% of the patients had a ctDNA progression earlier than radiologic progression, and 42% a ctDNA progression earlier than CA19-9 progression, both with a median lead time of about 2 months, which is supported by previous reports [ 46 , 79 ]. In resected PDAC, ctDNA could predict recurrence with a median lead time of 84 days.…”
Section: Discussionsupporting
confidence: 89%
“…We found that high abundances of KRAS mutations in ctDNA at baseline and the second and third measurements were significantly and independently associated with poorer OS and PFS among patients with mPDAC receiving NPS chemotherapy. Multiple previous studies [ 31 , 46 54 ] supported that mutated KRAS in ctDNA predicted poorer survival in patients receiving chemotherapy, despite the different regimens used. KRAS-G12D mutation, which took up 51% of all cases in our study, is linked to even shorter survival than KRAS-G12V and other mutations [ 55 ].…”
Section: Discussionmentioning
confidence: 96%
“…Pathogenic alterations re ect the tumor mutational load and can be used to monitor treatment response and to identify resistance mutations at progression. [38][39][40] Type of neoadjuvant chemotherapy is still a matter of debate. [9,10] Considering the purpose of this approach, identifying genetic alterations to guide treatment decisions would be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…They were detected in baseline plasma, disappeared after neoadjuvant treatment prior to surgery, and were again detected at a higher VAF in the sample taken at progression. Pathogenic alterations reflect the tumor mutational load and can be used to monitor treatment response and to identify resistance mutations at progression 42 , 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%